Dietary Zinc Supplementation Prevents Autism Related Behaviors and Striatal Synaptic Dysfunction in Shank3 Exon 13–16 Mutant Mice - Fourie, Chantelle; Vyas, Yukti; Lee, Kevin; Jung, Yewon; Garner, Craig C.; Montgomery, Johanna M. (Frontiers in Cellular Neuroscience, 2018)
The SHANK family of synaptic proteins (SHANK1–3) are master regulators of the organizational structure of excitatory synapses in the brain. Mutations in SHANK1–3 are prevalent in patients with autism spectrum disorders (ASD), and loss of one copy of SHANK3 causes Phelan-McDermid Syndrome, a syndrome in which Autism occurs in >80% of cases. The synaptic stability of SHANK3 is highly regulated by zinc, driving the formation of postsynaptic protein complexes and increases in excitatory synaptic strength. As ASD-associated SHANK3 mutations retain responsiveness to zinc, here we investigated how increasing levels of dietary zinc could alter behavioral and synaptic deficits that occur with ASD. We performed behavioral testing together with cortico-striatal slice electrophysiology on a Shank3−/− mouse model of ASD (Shank3ex13–1616−/−), which displays ASD-related behaviors and structural and functional deficits at striatal synapses. We observed that 6 weeks of dietary zinc supplementation in Shank3ex13–16−/− mice prevented ASD-related repetitive and anxiety behaviors and deficits in social novelty recognition. Dietary zinc supplementation also increased the recruitment of zinc sensitive SHANK2 to synapses, reduced synaptic transmission specifically through N-methyl-D-aspartate (NMDA)-type glutamate receptors, reversed the slowed decay tau of NMDA receptor (NMDAR)-mediated currents and occluded long term potentiation (LTP) at cortico-striatal synapses. These data suggest that alterations in NMDAR function underlie the lack of NMDAR-dependent cortico-striatal LTP and contribute to the reversal of ASD-related behaviors such as compulsive grooming. Our data reveal that dietary zinc alters neurological function from synapses to behavior, and identifies dietary zinc as a potential therapeutic agent in ASD.